Directly Measured vs. Calculated Low-Density Lipoprotein Cholesterol Does Not Identify Additional Individuals With Coronary Artery Disease and Diabetes at Higher Risk of Adverse Events: Insight From a Large Percutaneous Coronary Intervention Cohort in Asia - Shi, Boqun; Wang, Hao-Yu; Liu, Jinpeng; Cai, Zhongxing; Song, Chenxi; Jia, Lei; Yin, Dong; Wang, Hongjian; Dou, Ke-Fei; Song, Weihua (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: The objective of our study was to assess whether calculated low-density lipoprotein cholesterol (LDL-C) is inferior to direct LDL-C (dLDL-C) in identifying patients at higher risk of all-cause mortality, recurrent acute myocardial infarction (AMI), and major adverse cardiovascular event (MACE). METHODS: 9,751 patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention in the Fuwai PCI registry were included. DLDL-C was measured by the selective solubilization method (Kyowa Medex, Tokyo). Correct classification was defined as the proportion of estimated LDL-C in the same category as dLDL-C based on dLDL-C levels: less than 1.4, 1.4 to 1.8, 1.8 to 2.6, 2.6 to 3.0, and 3.0 mmol/L or greater. RESULTS: Underestimation of LDL-C was found in 9.7% of patients using the Martin/Hopkins equation, compared with 13.9% using the Sampson equation and 24.6% with the Friedewald equation. Cox regression analysis showed compared the correct estimation group, underestimation of LDL-C by the Martin/Hopkins equation did not reduce all-cause mortality (HR 1.26, 95% CI: 0.72-2.20, P=0.4), recurrent AMI (HR 1.24, 95% CI: 0.69-2.21, P=0.5), and MACE (HR 1.02, 95% CI: 0.83-1.26, P=0.9). Similarly, the overestimated group did not exacerbate all-cause mortality (HR 0.9, 95% CI: 0.45-1.77, P=0.8), recurrent AMI (HR 0.63, 95% CI: 0.28-1.44, P=0.3), and MACE (HR 1.07, 95% CI: 0.86-1.32, P=0.6). The results of the diabetes subgroup analysis were similar to those of the whole population. CONCLUSIONS: Compared with dLDL-C measurement, misclassification by the Martin/Hopkins and Sampson equations was present in approximately 20% of patients. However, directly measured vs. calculated LDL-C did not identify any more individuals in the PCI population with increased risk of all-cause mortality, recurrent AMI, and MACE, even in high-risk patients such as those with diabetes.